Effects of different temperatures on Leiocassis longirostris gill structure and intestinal microbial composition - Zhongmeng Zhao; Han Zhao; Xiongyan Wang; Lu Zhang; Chengyan Mou; Zhipeng Huang; Hongyu Ke; Yuanliang Duan; Jian Zhou; Qiang Li (Scientific Reports, 2024)
Abstract Fish are poikilothermic vertebrates and their physiological activities are affected by water temperature. In recent years, extreme weather has occurred frequently, and temperature changes have adversely affected the growth of farmed fish. To explore the changes in gill tissue structure caused by changing the water temperature and the relationship between the intestinal microbiota and the Leiocassis longirostris host adaptation mechanism, gill tissue sections and intestinal microbial 16S rRNA amplicon sequencing were conducted under different temperature stress (low temperature 4 °C, normal temperature 26 °C and high temperature 32 °C). The results showed that heat stress and cold stress caused injury and swelling, terminal congestion, cell vacuolation, and necrosis of the gill tissue of L. longirostris. For intestinal microbiota, the abundances of Pseudomonadota and Bacillota increased at the cold stress, while the abundances of Fusobacteriota and Bacteroidota increased at the heat stress. The number of opportunistic bacteria, mainly Aeromonas and Acinetobacter, was the highest under cold stress. In addition, the richness of the intestinal microbiota decreased significantly at heat and cold stresses, while evenness increased. Prediction of intestinal microbiota function showed that most common functions, such as metabolism of cofactors and vitamins, energy metabolism and replication and repair, were decreased significantly at heat stress and cold stress, and phylogenetic relationship analysis revealed significant differences among the groups. In conclusion, the change of temperature altered the gill tissue structure, and affected the structure and homeostasis of the intestinal microbiota, thus affecting the survival time of L. longirostris, and cold stress had a greater effect than heat stress.